The center of reference and assistance to women as an articulator of the network for the fight against violence against women: an empirical study of CRAM Tia Alice (Petrópolis/RJ) - Justen Gomes, Thais; Nunez Nascimento Lopes Salles, Denise Mercedes (Ius Humani. Jornal do direito, 2025)
The Maria da Penha Law (Law No. 11,340/06), a legislative milestone in the fight against domestic violence against women, is a public policy that connects to other policies aimed at combating gender-based violence, such as the National Plans for Policies for Women, the National Policy to Combat Violence against Women, and the National Pact to Combat Violence against Women. These policies promoted the creation and strengthening of the Network to Combat Violence against Women, which includes the Women's Assistance Reference Centers (CRAM). CRAM plays a fundamental role in providing multidisciplinary care, coordinating the support network, and preventing violence. Despite their importance, CRAMs have been scarcely explored from a legal standpoint. This study aimed to analyze the relevance of CRAM in the effective implementation of the Maria da Penha Law. The specific objectives are: (a) to examine the relationship between the Maria da Penha Law and public policies to combat violence in light of Maria Paula Dallari Bucci's concepts; and (b) to analyze the coordinating role of CRAM within the Network to Combat Violence, based on a case study of CRAM Petrópolis (CRAM Tia Alice), mapping its actions, user data, and the municipal law regarding the flowchart of care for women in situations of violence. Data from CRAM Tia Alice between 2018 and 2023 were examined, and a mapping of the service's actions from 2022 to 2024 was performed.